Libraries in 2014: 10 recipes to continue innovating - Lozano, Roser (Anuario ThinkEPI, 2014)
Based on the idea of a just-in-time library, not just-in-case, and a shift from supply to demand as the engine of management, 10 library innovation actions are proposed. Examples of these actions are: Less is more; Don’t buy, rent; No storage for just-in-case; Discard old habits and concepts; Make your library visible, etc.